2019
DOI: 10.1002/jcu.22712
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment of the maxillary artery and middle meningeal artery in the infratemporal fossa

Abstract: Purpose To investigate with Doppler ultrasonography the maxillary and middle meningeal arteries in the infratemporal fossa, and describe their hemodynamic characteristics. Methods We included 24 female and 11 male volunteers without vascular diseases, with a median age of 43 years. We used the acoustic window, enlarged by subjects half‐opening their mouth, located below the zygomatic arch, in front of temporo‐mandibular joint, to reach the maxillary and middle meningeal arteries. Results In the 35 subjects, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, meningeal vascular tone can vary independently of systemic arterial pressure. The middle meningeal artery has its own intrinsic independent autoregulation and only minimally (or differentially) responded to drugs able to induce larger changes in the other vascular beds (7578). Likewise, a study from Ashina and colleagues showed that while there were no differences in extracranial blood vessels during spontaneous migraines in humans, intracranial arteries had a slight dilation during the attacks (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, meningeal vascular tone can vary independently of systemic arterial pressure. The middle meningeal artery has its own intrinsic independent autoregulation and only minimally (or differentially) responded to drugs able to induce larger changes in the other vascular beds (7578). Likewise, a study from Ashina and colleagues showed that while there were no differences in extracranial blood vessels during spontaneous migraines in humans, intracranial arteries had a slight dilation during the attacks (13).…”
Section: Discussionmentioning
confidence: 99%
“…The technique to view the maxillary artery has been described in detail. 6 The artery is viewed in the infratemporal fossa between the condylar and coronoid processes of the mandible. The temporomandibular joint must be semi-depressed to allow an optimum window.…”
Section: Discussionmentioning
confidence: 99%
“…Lepic et al visualised it in 85% of their patients. 6 The involvement of the maxillary artery in GCA is supported on clinical and anatomical grounds. Chewing diffi culties and jaw claudication are present in up to 45% of individuals with GCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several imaging studies have described the close relationships between the maxillary and middle meningeal arteries and osseous structures [7][8][9][10][11][12]. However, the minimal distances between these structures remain difficult to predict for an individual patient; at present, it is not possible to generally delimit a safe surgical region.…”
Section: Introductionmentioning
confidence: 99%